Study of Binary and Ternary Solid Dispersion of Spironolactone Prepared By Co-Precipitation Method for the Enhancement of Oral Bioavailability - Mohammad Fahim Kadir, Md. Rashedul Alam, Akib Bin Rahman, Yeakuty Marzan Jhanker, Tahiatul Shams, Rajibul Islam Khan (Journal of Applied Pharmaceutical Science)
The study was designed to formulate novel spironolactone, a BCS class II drug loaded solid dispersion system (SDs) with improved dissolution rate. For this purpose binary and ternary solid dispersion were prepared by co-precipitation method using Poloxamer-407 only and mixture of poloxamer-407 with a second polymer such as HPMC 6cps, HPC, Kollicoat IR, Kollidon VA 64 respectively. To prepare binary SDs poloxamer 407 was used in three concentrations: 33%, 50% and 66.67% wt/wt of total SDs, whereas in case of ternary SDs, poloxamer 407 was used at 15%, 25% 35% wt/wt of the total SDs content and the concentration of the second polymer is maintained at fixed amount (1gm). In vitro dissolution study was carried out in a USP type II dissolution apparatus in 0.1 N hydrochloric acid solution for 1 hour. Release property of spironolactone from two different SDs was examined. Both the systems showed improved release profile compared with pure spironolactone powder. Enhanced release of spironolactone from the optimized SDs was characterized in light of cumulative percent release, % release after 5 min of dissolution and release rate of the drug from different SDs. When the amount of carriers increased with a decrease in drug content, the release of spironolactone was elevated. And it was found that almost two fold increase in the release of spironolactone while 66.67% poloxamer was used.
Keywords: Solid dispersion,Spironolactone,Co-precipitation,poloxamer-407,Dissolution.